2016
DOI: 10.1152/ajpheart.00246.2016
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous nitric oxide derived from NOS I or II in thoracic spinal cord exerts opposing tonic modulation on sympathetic vasomotor tone via disparate mechanisms in anesthetized rats

Abstract: The sympathetic preganglionic neurons (SPN) in the thoracic spinal cord regulate vasomotor tone via norepinephrine released from sympathetic terminals and adrenal medulla. We assessed the hypothesis that nitric oxide synthase I (NOS I)- and NOS II-derived nitric oxide (NO) in the thoracic spinal cord differentially modulate sympathetic outflow and that the adrenal medulla may be involved in those modulatory actions. In Sprague-Dawley rats, NOS I immunoreactivity was distributed primarily in the perikaryon, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Moreover, intrathecal Arg maintains mean blood pressure during hemorrhage in anesthetized rats (Malik et al, 2007 ). While these findings support a hypothetical NO-mediated activation of vasomotor tone in the spinal cord, a recent study demonstrates that NO produced by NOS-I in SPNs contributes to maintain while NO produced by NOS-II in the vicinity of the intermediate lateral cell column tonically depress mean arterial blood pressure (Poon et al, 2016 ). By direct neural recordings, it has been demonstrated that intrathecal Arg increases renal sympathetic nerve activities in anesthetized rabbits (Hakim et al, 1995 ).…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, intrathecal Arg maintains mean blood pressure during hemorrhage in anesthetized rats (Malik et al, 2007 ). While these findings support a hypothetical NO-mediated activation of vasomotor tone in the spinal cord, a recent study demonstrates that NO produced by NOS-I in SPNs contributes to maintain while NO produced by NOS-II in the vicinity of the intermediate lateral cell column tonically depress mean arterial blood pressure (Poon et al, 2016 ). By direct neural recordings, it has been demonstrated that intrathecal Arg increases renal sympathetic nerve activities in anesthetized rabbits (Hakim et al, 1995 ).…”
Section: Discussionmentioning
confidence: 84%
“…Intrathecal administration of nociceptin (1, 2, or 5 nmol) in ICR mice elicited a significant and dose-dependent decrease in MAP and HR over our 60 minute observation period ( Figure 2 ). The power density of the low-frequency (BLF) component of SBP spectrum, an experimental index for spontaneous baroreflex-mediated sympathetic vasomotor tone, 30 33 also underwent a dose-dependent reduction over a time course that paralleled the changes in MAP. At the same time, the BRS, an experimental index for spontaneous cardiac vagal baroreflex, 31 , 34 exhibited a dose-dependent increase that mirrored the decrease in HR.…”
Section: Resultsmentioning
confidence: 99%
“…The recorded BP signals from the femoral artery were processed by an arterial BP analyzer (Notocord, Croissy-Sur-Seine, France) and the systolic blood pressure (SBP) signals were simultaneously subject to online and real-time spectral analysis (Notocord) to detect the power density of the low-frequency component of SBP spectrum (BLF; 0.15–0.6 Hz). 30 , 31 The power density of this spectral band has been demonstrated to be a valid experimental index for spontaneous baroreflex-mediated sympathetic vasomotor tone. 30 33 To evaluate the spontaneous cardiac vagal baroreflex, we employed a baroreflex sequence analyzer (Notocord) to determine baroreflex sensitivity (BRS) based on online detection of spontaneous sequences of consecutive increases or decreases in SBP associated with parallel changes in HR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recorded BP signals from the femoral artery were processed by an arterial BP analyzer (Notocord, Croissy-Sur-Seine, France) and the systolic blood pressure (SBP) signals were simultaneously subject to online and real-time spectral analysis (Notocord) to detect the power density of the low-frequency component of SBP spectrum (BLF; 0.15-0.6 Hz). 30,31 The power density of this spectral band has been demonstrated to be a valid experimental index for spontaneous baroreflex-mediated sympathetic vasomotor tone. [30][31][32][33] To evaluate the spontaneous cardiac vagal baroreflex, we employed a baroreflex sequence analyzer (Notocord) to determine baroreflex sensitivity (BRS) based on online detection of spontaneous sequences of consecutive increases or decreases in SBP associated with parallel changes in HR.…”
Section: Determination Of Bp Hr and Spontaneous Baroreflexmentioning
confidence: 99%